Indicators of Quality of Clinical Care for Type 2 Diabetes Patients in Primary Health Care Centers in Qatar: A Retrospective Analysis. (5th December 2019) - Attal, Saleh; Mahmoud, Mohamed H.; Aseel, Muna Taher; Candra, Ady; Amuna, Paul; Elnagmi, Mohamed; Abdallah, Mostafa; Ismail, Nahed; Abdelrazek, Ahmed; Albaw, Dia; Albashir, Abdulsalam; Elmahdi, Hisham
Abstract : Background . Despite the high prevalence of type 2 diabetes mellitus in Gulf countries, standards of diabetes care at the primary care level have not been widely studied. Aim . To compare the results of diabetes clinical indicators from the American Diabetes Association (ADA) 2017 guidelines to the reference benchmarks in the Behavioral Risk Factor Surveillance System. Materials and Methods . A cross-sectional analysis of electronic medical records in 643 randomly selected adult patients with type 2 diabetes was undertaken. A checklist enabled the collection of sociodemographic, clinical, biochemical, and quality measurement data. Data were analyzed using Stata 9.0. The chi-squared test was used to compare two or more proportions. Results . There were 643 patients (male = 60.3%; female = 39.7%), and the majority (71.7%) aged between 40 and 64 years. Common comorbidities were dyslipidemia (72.3%), hypertension (70%), obesity (50.1%), and preobesity (overweight) (37.9%). Over 15% were smokers. The most commonly prescribed diabetes medications were metformin (89.9%), dipeptidyl peptidase-4 inhibitors (61.1%), and sulfonylureas (49.3%). Only 35.5% (p < 0.0001 ) of patients met the reference glycated hemoglobin (HbA1c) cutoff level of 7.0%. The reference level for blood pressure control was met by 70.2% (p < 0.0001 ) and for low-density lipoprotein cholesterol, 73.8% (p < 0.0001 ). Albuminuria was present in 39.2%, and very low vitamin D level (<20 ng/ml) in 39.1%. Most patients had annual foot (89.6%, p < 0.0001 ) and eye (72.3%, p < 0.0001 ) examinations. Only 39.9% had referrals for dietary counseling, and there were lower rates of referrals and uptake for pneumococcal, influenza, and hepatitis B vaccines. Most (76.2%) did not have screening for depression. Conclusion . The majority of the results met the ADA standards, while glycemic control, dietary counseling, and screening for depression were poor in comparison to the standards. Continuing education for clinicians, patient education for self-management, and targeted weight management are recommended.